Educational performance between the human resource's theoretical paradigm and the practical mentality. Analysis at the European level - Ionescu, Romeo Victor; Zlati, Monica Laura; Antohi, Valentin Marian; Cristache, Nicoleta; Raducan, Monica (Frontiers in Psychology, 2022)
The issue of performance in education is permanently topical because it plays an important role in creating the most valuable resource: the labor. The aspect has been treated both from a scientific and applicative point of view through numerous strategies and optimization techniques, being integrated in the strategies for the education development as a training system at a global level. The objective of this research is to identify the need for performance and assess the theoretical and practical dimension of the European gap in performance in education, given the impact of the global crisis. The analysis was based on a structured questionnaire, part of a pilot research in which a number of 130 teachers and school managers from Romania and 97 teachers and school managers from five other European countries participated. The results of the study will allow the identification of the human resource’s theoretical paradigm and the practical mentality in the education system in order to improve performance, the authors proposing to identify concrete applicable measures on short term.